The challenges and opportunities experienced during COVID-19 inform reshaping of teaching, learning and research practices for a subgroup of FPP participants - Hadebe, S.; Williams, A.; Sifolo, P.; Bradley, M.; Abduroaf, M. (South African Journal of Higher Education, 2024)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and subsequent coronavirus disease 2019 (COVID-19) had widespread disruptive consequences on various sectors including tertiary education. Universities were shut down and forced to introduce emergency remote teaching and learning. This coincided with the period where the authors of this article started advanced professorial training through the Future Professors Programme Phase 2, Cohort 1 (FPP). Like other educators, the authors experienced COVID-19-linked challenges and opportunities and decided to report on this through a review of the literature and reflective writing. While most publications between 2020 and now focused on the challenges and opportunities caused by the pandemic within the teaching and learning environment, challenges and opportunities experienced in the research environment were less reported on. Often, the findings presented also focused on one discipline or in single institutions. This meant that the responses to address pandemic-associated disruptions would be limited in its view and weighted to teaching and learning and specific discipline(s). Set against the background of the South African higher education (HE) system, the authors review how COVID-19 augmented existing challenges as well as how it presented opportunities for improved teaching, learning and research. This is done by providing context to the challenges and opportunities of not only teaching and learning but of the research environment whilst focusing on several disciplines and institutions. While there is an overlap in the COVID-19 experience within the five Institutions (UCT, UWC, UJ, NWU and TUT) in terms of challenges and opportunities, the impact on research was as devastating as it was on teaching and learning with unique scenarios applicable to the respective disciplines/institutions. The supplemental FPP training and teachings placed the authors in a unique position compared to our peers, in our approach to dealing with the academic disruption. While the pandemic had a general negative outlook for most academics, the FPPs programme better prepared the authors to reimagine and reshape our teaching, learning and research practices to face future pandemics.